The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/jssc.201401071
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and enrichment of polycyclic aromatic hydrocarbons by ordered mesoporous carbon reinforced hollow fiber liquid‐phase microextraction

Abstract: A novel microextraction method, ordered mesoporous carbon reinforced hollow fiber liquid-phase microextraction coupled with high-performance liquid chromatography and fluorescence detection, was developed for the determination of some organic pollutants in water samples. Four polycyclic aromatic hydrocarbons (fluorene, anthracene, fluoranthene, and pyrene) were selected to validate this new method. Main parameters that could influence the extraction efficiency such as extraction time, fiber length, stirring ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 50 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…So ordered SBA‐15‐NH 2 could guarantee high binding capacity and good site accessibility for target molecules based on the benefits above, therefore it has enticed considerable attention in many fields such as catalysis, biomedicine, separation, and environment remediation . The types of mesoporous material families have been developed with diverse morphologies such as fibers , films , polyhedral particles , and spheres . Combination of SPE methods with ultrasound radiation provides an efficient technique for extraction of various analytes at trace concentrations .…”
Section: Introductionmentioning
confidence: 99%
“…So ordered SBA‐15‐NH 2 could guarantee high binding capacity and good site accessibility for target molecules based on the benefits above, therefore it has enticed considerable attention in many fields such as catalysis, biomedicine, separation, and environment remediation . The types of mesoporous material families have been developed with diverse morphologies such as fibers , films , polyhedral particles , and spheres . Combination of SPE methods with ultrasound radiation provides an efficient technique for extraction of various analytes at trace concentrations .…”
Section: Introductionmentioning
confidence: 99%
“…Many sample preparation methods have been reported for the extraction of PAHs such as LLE , hollow‐fiber LPME , SPE , SPME , stir bar sorptive extraction , stir rod sorptive extraction , and magnetic SPE . Among these methods, SPE is the most widely used due to its high extraction efficiency, high enrichment factor, low solvent consumption, and ease of operation .…”
Section: Introductionmentioning
confidence: 99%
“…Humans are exposed to PAHs from numerous sources. Such exposures can occur in occupational settings, from the environment , from cigarette smoking , from vehicular exhaust emissions , water , and so on. Cell experiments indicated that carcinogenic PAHs induced reactive oxygen species, triggered oxidative DNA damage, and compromised DNA repair .…”
Section: Introductionmentioning
confidence: 99%